2021
DOI: 10.33594/000000469
|View full text |Cite
|
Sign up to set email alerts
|

Cell Volume Regulation Mechanisms in Differentiated Astrocytes.

Abstract: BACKGROUND/AIMS: The ability of astrocytes to control extracellular volume homeostasis is critical for brain function and pathology. Uncovering the mechanisms of cell volume regulation by astrocytes will be important for identifying novel therapeutic targets for neurological conditions, such as those characterized by imbalances to hydro saline challenges (as in edema) or by altered cell volume regulation (as in glioma). One major challenge in studying the astroglial membrane channels involved in volume homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
(115 reference statements)
0
15
0
Order By: Relevance
“…It is known that CaMKII is activated by CaM upon increase of cytosolic Ca 2+ . Increased cytosolic Ca 2+ due to cell swelling has also been shown to activate ICl,swell in astrocytes [63,64]. These results identify Ca 2+ as a key player in the activation pathways of both MLC1 and ICl,swell.…”
Section: Hyposmosis Induces Ca 2+ Influx and Ca 2+ Release In U251 Cells: Role Of Extracellular Ca 2+ Influx In Camkii/mlc1-dependent Enhmentioning
confidence: 79%
“…It is known that CaMKII is activated by CaM upon increase of cytosolic Ca 2+ . Increased cytosolic Ca 2+ due to cell swelling has also been shown to activate ICl,swell in astrocytes [63,64]. These results identify Ca 2+ as a key player in the activation pathways of both MLC1 and ICl,swell.…”
Section: Hyposmosis Induces Ca 2+ Influx and Ca 2+ Release In U251 Cells: Role Of Extracellular Ca 2+ Influx In Camkii/mlc1-dependent Enhmentioning
confidence: 79%
“…To observe actin dynamics in more in vivo -like cell culture conditions, we used two different approaches: i) astrocytes plated on a nanostructured surface, with starlike shapes and more realistic molecular and functional features devoted to homeostatic control of potassium concentrations and cell volume [79, 77], and ii) co-culture of astrocytes with primary cortical neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that astrocytes grown on HTlc are more efficient in their homeostatic process. In particular, the expression and function of Kir4.1 and water channel aquaporin 4 (AQP4) as well as the functional response to anisotonic challenge are enhanced in differentiated [77,79] and mature [117][118][119][120][121][122] cells. A more efficient response to homeostatic challenges due to the higher levels of channel proteins may be related to the weaker actin dynamics observed in differentiated cells compared to polygonal cells (both with and without neurons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerol permeability in HCT8 cells was measured using a calcein-quenching method (Mola et al, 2009;Mola et al, 2021). Nearly 80% of confluent cells were grown on 40-mm glass coverslips.…”
Section: Glycerol Permeability Assaymentioning
confidence: 99%